EXAMINATION OF RHYTHMIC GYMNASTS ATTITUDES TOWARDS HEALTHY NUTRITION AND SOCIAL PHYSIQUE CONCERNS - Duygu Doğan; Nevin Gündüz; Semiyha Tuncel (Science of Gymnastics Journal, 2025)
The aim of this research is to examine rhythmic gymnastics athletes' attitudes towards healthy nutrition and their social physique concerns. The population of the study consists of active rhythmic gymnastics athletes aged 12 and above who have participated in competitions organized by the Turkish Gymnastics Federation for at least three years. The sample includes 90 volunteer rhythmic gymnastics athletes who meet these criteria. The Personal Information Form, Healthy Nutrition Attitude Scale, and Social Physique Anxiety Inventory were used as data collection tools. The Personal Information Form collected data regarding the athletes’ national athlete status, the age category in which they compete, and the number of years they have participated in rhythmic gymnastics competitions. A survey model was employed as the research method. The data were analyzed using SPSS 21 software. Descriptive statistics, Independent Samples t-test, One-Way Analysis of Variance (ANOVA), and Pearson Correlation Analysis were applied. A statistically significant difference was found in athletes’ “Expectations of Negative Evaluation” scores based on years of competition and age category (p < 0.05). Additionally, according to the age category variable, statistically significant differences were observed in the “Emotion for Nutrition” and “Malnutrition” subdimensions (p < 0.05). A strong relationship was also found between athletes’ “Emotion for Nutrition” scores and their social physique concerns. As a result, it has been observed that as rhythmic gymnastics athletes grow older and gain more experience, their social physique concerns increase, malnutrition tendencies decrease, and their emotional engagement with nutrition improves.